1997
DOI: 10.1172/jci119160
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide binding protein and soluble CD14 catalyze exchange of phospholipids.

Abstract: Lipopolysaccharide binding protein (LBP) is a plasma protein known to facilitate the diffusion of bacterial LPS (endotoxin). LBP catalyzes movement of LPS monomers from LPS aggregates to HDL particles, to phospholipid bilayers, and to a binding site on a second plasma protein, soluble CD14 (sCD14). sCD14 can hasten transfer by receiving an LPS monomer from an LPS aggregate, and then surrendering it to an HDL particle, thus acting as a soluble "shuttle" for an insoluble lipid. Here we show that LBP and sCD14 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
156
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(163 citation statements)
references
References 25 publications
5
156
0
2
Order By: Relevance
“…We have previously observed that the fluorescence of FITC-LPS is enhanced when LBP complexes to the LPS (7), and others have observed the same phenomenon with Bodipy-LPS (8). Based on the sedimentation properties of LPS-LBP complexes, we have speculated that the increase in fluorescence was due to a reduction in fluorescein self-quenching resulting from disaggregation of LPS by LBP (7).…”
Section: Comparison Of Effects Of Lbp and Bpi On Fitc-lps-mentioning
confidence: 61%
“…We have previously observed that the fluorescence of FITC-LPS is enhanced when LBP complexes to the LPS (7), and others have observed the same phenomenon with Bodipy-LPS (8). Based on the sedimentation properties of LPS-LBP complexes, we have speculated that the increase in fluorescence was due to a reduction in fluorescein self-quenching resulting from disaggregation of LPS by LBP (7).…”
Section: Comparison Of Effects Of Lbp and Bpi On Fitc-lps-mentioning
confidence: 61%
“…There are controversial reports of the linkage between H. pylori infection and atherosclerosis [18]. sCD14 contributes to lipid metabolism, as sCD14 transports lipids and LPS to high-density lipoprotein (HDL) [31,32]. Dysfunctional lipid metabolism is a characteristic feature of several infections [33].…”
Section: Discussionmentioning
confidence: 99%
“…The role of CD14, LBP, and TLRs in LPS signaling has been well supported by studies in animal models (13)(14)(15)(16). Besides its function in endotoxin signaling, it has been proposed that CD14 is involved in transportation of other lipids (17,18), cell-cell interaction during different immune responses (19 -21), and recognition of apoptotic cells (22,23). Therefore, CD14 becomes an interesting molecule to investigate in various biological processes.…”
mentioning
confidence: 98%